(untitled) (Research, Society and Development, 2022)
The objective was to analyze the association of maternal morbidities in the periods of pregnancy, childbirth, and puerperium among Maxakali women, in the cities of Bertópolis and Santa Helena de Minas, considering the place of delivery (home versus hospital) from 2004 to 2013. Cross-sectional, retrospective and quantitative study with non-nominal data, from the Health Information System for Indigenous Peoples. The rates of home and hospital births of 224 pregnant women with 719 pregnancies were 63% and 24.3%, respectively. Of the 284 identified morbidities, 68% occurred during pregnancy, 12.7% during childbirth, and 19.4% during the postpartum period. During pregnancy, maternal morbidity was 2.5 times higher for deliveries that took place in the village, when compared to deliveries that took place in the hospital (OR: 2.54 - CI: 1.52 - 2.66). For childbirth, the occurrence of maternal morbidities was observed less frequently in home births (OR: 0.19 – CI: 0.1 - 0.47), with 81% fewer morbidity complications for this group. This fact is due to the place of delivery and a sum of factors such as prenatal care; articulation between the two systems; examinations during pregnancy, among others. The chance of developing puerperal morbidity was 2.1 times greater in the group of pregnant women whose delivery took place at home when compared to hospital delivery (OR: 2.1 - CI: 1.14 - 3.58). Hospital delivery proved a protective factor for maternal complications in the puerperium. It is hoped that this work will support new epidemiological studies on indigenous maternal morbidity and mortality.